2003
DOI: 10.1021/jm0302086
|View full text |Cite
|
Sign up to set email alerts
|

Metabolites of Febrifugine and Its Synthetic Analogue by Mouse Liver S9 and Their Antimalarial Activity against Plasmodium Malaria Parasite

Abstract: Quinazolinone type alkaloids, febrifugine (1) and isofebrifugine (2), isolated from Dichroa febrifuga roots, show powerful antimalarial activity against Plasmodium falciparum. Unfortunately, their emetic effect and other undesirable side effects have precluded their clinical use for malaria. Because of their antimalarial potency, analogues were searched for, with the goal of preserving the strong antimalarial activity, while dramatically reducing side effects. We expected that compounds useful in drug developm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(40 citation statements)
references
References 14 publications
1
39
0
Order By: Relevance
“…Because mice do not possess a vomiting reflex, the emetic effects could not be observed in tests with mice. However, the mice treated subcutaneously in our tests did not display apparent diarrhea or gastrointestinal tract hemorrhage, similar to data reported previously (6). This phenomenon implies that the diarrhea and intestinal hemorrhage caused by febrifugine analogs are acquired merely through contact with the host gastrointestinal tract.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Because mice do not possess a vomiting reflex, the emetic effects could not be observed in tests with mice. However, the mice treated subcutaneously in our tests did not display apparent diarrhea or gastrointestinal tract hemorrhage, similar to data reported previously (6). This phenomenon implies that the diarrhea and intestinal hemorrhage caused by febrifugine analogs are acquired merely through contact with the host gastrointestinal tract.…”
Section: Discussionsupporting
confidence: 91%
“…For example, it was found that the administration of febrifugine analogs did not cause changes to body or liver weights, irritation of the gastrointestinal tract, or alteration of the levels of hepatic enzyme markers in infected mice (6,20). Febrifugine altered the production of nitric oxide and tumor necrosis factor alpha in mouse macrophages (19).…”
mentioning
confidence: 99%
“…Several compounds that have a high binding constant (docking score) to the region containing C106 (C106 region) but not to other regions were obtained. Structures of compounds A and B (Kametani et al 1974a,b), which had the highest docking score to the C106 regions of reduced and of oxidized DJ-1 as the SO 2 H form, respectively, and the structure of compound C (Hirai et al 2003), which had the lowest docking score to oxidized DJ-1, are shown in Fig. 1(b).…”
Section: Identification Of Dj-1-binding Compoundsmentioning
confidence: 99%
“…24) had antimalarial activity against P. falciparum, of similar potency to that of natural product febrifugine, with high selectivity. 223 The results also suggest that basicity of both the 1-and the 1 00 -nitrogen atoms of febrifugine is crucial in conferring powerful antimalarial activity. Compound 124 exhibited highest in vivo antimalarial activity against P. berghei, with no serious side effects (ED 50 ¼ 0.6 mg/kg).…”
Section: J Natural Product Based Antimalarial Agentsmentioning
confidence: 93%